SCIENTIFIC AND PUBLIC ORGANIZATIONS OF THE REGION CAUCASIAN MINERAL WATERS AT THE TURN OF XIX-XX CENTURIES AND THEIR CONTRIBUTION TO THE DEVELOPMENT OF RESORTS - Yulia Fedorovna Zolnikova (Наука. Инновации. Технологии, 2022)
Balneology, medical, mining, and other scientific and public organizations were established in the North Caucasus, including in the region of Caucasian Mineral Waters in the XIX-XX centuries. They conducted medical and geographical studies of therapeutic factors in the region, to develop measures for the development of resorts and organizing various recreational activities in the Caucasian Mineral Waters. This period was very important for the quantity and significance of such research. Such societies have played a major role in the history of development of domestic balneology and development of resorts. This article shows the historical activity of balneological and medical societies that have made a signiicant contribution to the development of recreational resources, the development of recreational activities in the holiday region and the establishment of city-resort in the region Caucasian Mineral Waters.